Differences in Characteristics and Income of Duck Farming in Sukra and Sindang Districts, Indramayu Regency - Herlina, Linda; Firmansyah, Cecep; Salsabilah, Khansa Nurul (Jurnal Ilmu Ternak Universitas Padjadjaran, 2023)
AbstractDuck is one of the commodities breeders rely on in Indramayu Regency as a source of income to support the farmer's family expenses. Two areas became the basis for providing duck products in Indramayu Regency: Sukra District and Sindang District. The purpose of this study was to determine the difference in the average characteristics of the breeder's variables consisting of livestock experience, age, number of family members out of the farmer, distance to marketing centers, farmer expenses, duck farming costs, duck farming revenue, and farmer income (per head per year). The method used was a survey with 100 farmers as respondents. Data were collected using interviews with questionnaires. The results showed that to conduct a valid independent sample t-test, several steps were needed, namely removing outliers and variables that did not have normally distributed data. This process produces 4 valid variables used in the difference test. In the end, the variables significantly different between duck farmers in Sukra and Sindang Districts were the average age of the breeders and the average cost of raising ducks. This is because the sources of production inputs used are different from each other, and optimizing the use of production factors is not easy due to the relatively small number of livestock, which is less than 1000 heads per farmer.